Inner-shell ionization of W25+. Issue 15 (January 2020) - Pakalka, S; Kynienė, A; Jonauskas, V
Synopsis: Inner-shell ionization by electron impact is investigated for the W 25+ ion. Decay of inner-shell vacancy through Auger transitions is analyzed. Contribution of direct ionization process to double and triple ionization is presented.